THE ENHANCEMENT OF GIVING REASON SKILL AND EXCITING CONCLUSION SKILL AND MASTERY OF CONCEPT ON REDUCTION OXIDATION REACTION MATERIAL BY PROBLEM BASED LEARNING MODEL - Sulastri Sulastri; Ila Rosilawati; Noor Fadiawati (Universitas Lampung, 2012)
The aim of this research were to find out and to describe enhancement of giving reason skill and exciting conclusion skill and mastery of concept by problem based learning on reduction oxidation reaction material. The population of this research was all student of the first grade of SMAN 1 Rumbia in academic year 2011-2012 where class X4 and class X5 were the sample of the research. this research used a quasi experiments method with non equivalent control group design and parametric test with t' test. The effectiveness of problem based learning model was measured based on the increasing of significant n-Gain. The result of the research showed that n-Gain average of giving reason skill for eksperimen class and control class was 0,46 and 0,31; n-Gain average of exciting conclusion skill for eksperimen class and control class was 0,51 and 0,17; and n-Gain average of mastery of concept for eksperimen class and control class was 0,41 and -0,51.Based on hypotesis testing, it is known that student in experiment class where was applied by problem based learning model had higher giving reason skill, exciting conclusion skill and mastery of concept than the class that applied conventional learning. It is proved that problem based learning model was effective in increasing giving reason skill, exciting conclusion skill and mastery of concept on reduction oxidation reaction material.Keyword: problem based learning, giving reason skill, exciting conclusion skill, mastery of concept.